Construction Site Workers’ Awareness on Using Safety Equipment : Case Study - Md Ulang, N.; Salim, N. S.; Baharum, F.; Agus Salim, N.A. (EDP Sciences, 2014)
Construction sector is an important sector and contributed significantly to national development. However, this sector poses higher risk to accident. This is due to fact that construction site can be considered as a dangerous zone to workers and to the public. Due to the variety of cases occurs on site, the contractor will usually have to pay the cost related to accidents in the form of higher insurance premium. Despite various measures, accidents still occur at construction sites. Personal Protective Equipment (PPE) is one of the important means to protect the wearer from hazards in the workplace. Since this equipment is the last frontier of the wearer from worksite hazards, it is important to select it based on the job scope and the intended protection. Therefore, this study was formulated to find out the level of knowledge and awareness of construction workers on PPE usage. It was also important to know what make the workers would want or do not want to use the PPE. It was found in this study that the level of awareness and knowledge among workers on the proper use of PPE is moderate. Construction sites accident can be further be reduced with proper implementation of PPE voluntarily by all workers.